BENEFITS OF E-WALLET APPLICATIONS FOR STUDENT TRANSACTIONS - avy antika; Annisah Annisah; Wira Handayani (Universitas Muhammadiyah Bengkulu, 2022)
Digital wallet (e-wallet) is one of the digital financial products. E-wallet is considered as a more effective non-cash payment alternative. Electronic money is generally stored in digital wallets for easy access. With the current trend of digital wallets that offer benefits, convenience and effectiveness in student payment transactions, it will be easier for students to spend their money so that it will affect student consumptive behavior. The objectives of this study include 1) knowing the benefits of digital wallets on student retail transactions seen from the increase in online transportation orders, online food orders, and e-commerce transactions. 2) To find out whether digital wallets affect student consumptive behavior seen from the increase in transactions. 3) To find out whether digital wallets have an influence on student lifestyles. The research method used is descriptive qualitative where the subjects of this research are students of the Muhammadiyah University of Riau, the Faculty of Economics and Business Class of 2019 and users of digital wallets. The result achieved is that digital wallets have a significant and significant influence on the consumptive behavior of students. An easy, safe, efficient and innovative digital wallet has increased student retail transactions, especially for retail transactions, namely online transportation and food orders.